Inhibition of renin-angiotensin axis reduces the risk of thrombus formation in the left atrial appendage in patients with hypertension complicated by atrial fibrillation. (June 2018) - Suo, Ya; Zhang, Zhiwei; Fu, Huaying; Zhang, Yue; Yuan, Meng; Wang, Yuanyuan; Goudis, Christos A; Tse, Gary; Liu, Tong; Li, Guangping
Aims: We examined whether the use of a renin-angiotensin-aldosterone system (RAS) inhibitor plays a role in protecting against left atrial appendage thrombus (LAAT) in patients with hypertension complicated by atrial fibrillation (AF). Methods: Two observational studies were conducted on patients with diagnoses of hypertension and AF, who were categorized into RAS inhibitor user or nonuser groups. Demographic characteristics, clinical characteristics, echocardiographic parameters and hemostatic markers were examined and the occurrence of LAAT during follow-up were recorded. Results: In the first study ( n = 131), LA peak systolic strain and LAA emptying flow velocity (LAA eV) were significantly increased in patients on RAS inhibitors compared with the nonuser group ( p < 0.05). Lower D-dimer and fibrinogen levels were observed in patients on RAS inhibitors ( p < 0.05). In the second study ( n = 99), 25.9% ( n = 11) of patients on RAS inhibitors developed LAAT, compared with 46.7% ( n = 21) in the nonuser group ( p < 0.05). After controlling for risk factors related to LAAT, use of RAS inhibitors remained associated with a significantly lower risk of developing LAAT (HR, 0.406; 95% CI, 0.191–0.862; p = 0.019). Conclusions: RAS inhibitors use was associated with a significant reduction in the risk of LAAT in patients with hypertension and AF.